2007
DOI: 10.1590/s1677-55382007000200004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between PSA density, free PSA percentage and PSA density in the transition zone in the detection of prostate cancer in patients with serum PSA between 4 and 10 ng/ml

Abstract: The determination of %FPSA and PSAD can allow a better discrimination between PCa and benign disease that the isolated use of PSA. The combination of PSADTZ, %FPSA, TZV and age promote a high accuracy for PCa detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
1
10
1
3
Order By: Relevance
“…There was a significant difference between the two groups. The above three indices can be used for differential diagnosis between PCA and BPH [7] . Compared to the TPSA, a higher sensitivity of the 3 indices can be found in diagnosing PCA, however, there was no obvious difference among the 3 indices.…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant difference between the two groups. The above three indices can be used for differential diagnosis between PCA and BPH [7] . Compared to the TPSA, a higher sensitivity of the 3 indices can be found in diagnosing PCA, however, there was no obvious difference among the 3 indices.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic rate reached 22.9% when coupled with biopsy by ultrasonic guidance, given f/t PSA ratios under 0.10 and PSA content in the range of 2.5-4.0 ng mL −1 [27,28]. In addition, PSA density and PSA volocity were other important potential references for prostate cancer diagnosis [29,30]. At present, diagnostic strategies to detect prostate cancer in China still mainly rely on digital rectal examination and imaging.…”
Section: No Current Test Can Replace Serum Psa For Mass Scree Ning Ofmentioning
confidence: 99%
“…Since the dosing of serum PSA is accompanied by failure, variants of PSA measurements have been described in order to increase its accuracy: free/total PSA ratio, age-specific PSA, PSA density and PSA velocity (3). It was concluded that the combination of the PSA density, free PSA percentage and age are factors which contribute to high accuracy for PC detection (4). Despite the development of tools that help early diagnosis of organ-confined prostate cancer, up to 22% of newly diagnosed patients has been reported to have advanced or metastatic disease (5).…”
Section: Introductionmentioning
confidence: 99%